Scaled Model Simulation and Experimental Verification of Submarine Flexible Pipeline Laying System - Haixia Gong (MDPI AG, 2021)
In order to adapt to the complex and changeable marine environment such as wind, wave, and current, the physical simulation experiment is usually needed in the design of a deep-sea flexible pipeline-laying system. In reality, the flexible pipeline-laying system is very large, and the experimental cost is huge. Therefore, when analyzing this system, it is necessary to carry out scaled model experiments to verify the rationality of it. Taking the flexible pipeline-laying system working under four-level sea conditions as an example, this paper deduces the similarity criteria of the scaled model according to the similarity theory. According to the required experimental site, the sizes and materials of the model are selected, and then the physical quantities of the model and their similarity ratio corresponding to the prototype are determined. According to the physical quantities of the experimental model, the similarity of dynamic characteristics and structural strength between the model and the prototype are verified by Adams and ANSYS Workbench. The research shows that the scaled model and prototype based on similarity theory can meet the established similarity relationship, and the scaled model experiment is an effective way to verify the rationality of the design of a flexible pipeline-laying system.